Forensic investigation of methamphetamine tablets using physical and chemical profiling - Awang, Noor Azlina (2022)
Illicit methamphetamine seizures have reached record levels worldwide and its widespread use threatens societal well-being. Thus, attention from various parties is required to stem methamphetamine trafficking; however, routine forensic analysis is generally limited to identifying and quantifying the controlled substances according to standard operating procedures. Although further analytical characterization and drug profiling via physical and chemical methods is not routinely conducted, it warrants further exploration for forensic comparison and intelligence. In this study, evaluation of physical and chemical profiles of illicit methamphetamine tablets collected from case work was carried out through various analytical techniques, including physical examination, thin layer chromatography (TLC), attenuated total reflectance-Fourier transformed infrared (ATR-FTIR) spectroscopy, and lastly gas chromatography (GC). The analytical outputs were compared and evaluated for possible discrimination. Generally, physical characterisation did not enable the identification of methamphetamine with only six samples were discriminated from the main cluster through their unique logos and dimensions. Tablets with logo ―wY‖ dominated the samples (94.5%), and majority of them were measured between 6.01 and 6.20 mm in diameter (74.1%). ATR-FTIR coupled with PCA suggested caffeine as adulterant in majority of the samples (99.4%), while TLC analysis determined that Ponceau 4R was Illicit methamphetamine seizures have reached record levels worldwide and its widespread use threatens societal well-being. Thus, attention from various parties is required to stem methamphetamine trafficking; however, routine forensic analysis is generally limited to identifying and quantifying the controlled substances according to standard operating procedures. Although further analytical characterization and drug profiling via physical and chemical methods is not routinely conducted, it warrants further exploration for forensic comparison and intelligence. In this study, evaluation of physical and chemical profiles of illicit methamphetamine tablets collected from case work was carried out through various analytical techniques, including physical examination, thin layer chromatography (TLC), attenuated total reflectance-Fourier transformed infrared (ATR-FTIR) spectroscopy, and lastly gas chromatography (GC). The analytical outputs were compared and evaluated for possible discrimination. Generally, physical characterisation did not enable the identification of methamphetamine with only six samples were discriminated from the main cluster through their unique logos and dimensions. Tablets with logo ―wY‖ dominated the samples (94.5%), and majority of them were measured between 6.01 and 6.20 mm in diameter (74.1%). ATR-FTIR coupled with PCA suggested caffeine as adulterant in majority of the samples (99.4%), while TLC analysis determined that Ponceau 4R was the major dye added into the composition of the tablets (95.6%). Lastly, the GC technique confirmed the presence of methamphetamine (98.8%) through mass spectral comparison with similar index greater than 80% and the purity was determined. In conclusion, a methamphetamine tablet profiling strategy was implemented to gather important information regarding the similarities and differences among illicit methamphetamine tablets, potentially beneficial for sample-to-sample, case-to-case, and seizure-to-seizure comparisons.